Psychodiagnostics Of Personality Behavior Dispositions (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is devoted to the problem of personality disposition. Dispositions manifest themselves everywhere in various spheres of human life. Their manifestation in the educational environment has a certain specificity, which largely determines the characteristics of behavior and the quality of educational activities. The article presents the results of the study.